Teachers' and Learners' Attitudes Towards Error Correction in English as a Foreign Language Classes- Focus on Oral Error Correction Case of Second year Students at the Department of English, Mohamed-Cherif Messaadia University, Souk-Ahras - Imen KHEDRI (My University, 2022)
Abstract Error correction is an integral part of the foreign language teaching learning process. However, learning from one's errors will never be possible if the appropriate error correction strategies were not used, and if learners carry on holding negative perceptions about and negative attitudes towards their errors and their teachers' error treatment methods. Therefore, the current study aims to explore both teachers' and students' attitudes towards oral error correction. To achieve the research goals, and to test the hypothesis which states that if teachers use the appropriate strategies of oral error correction, learners' negative attitudes to error correction would be changed, an exploratory mixed method as an approach to combining qualitative and quantitative was used through the use of a questionnaire with fifteen teachers at the Department of English at Mohammed Cherif Messaadia University, and another one was administered to fifty three second year LMD students at the same department. So as to observe the way teachers deal with learners' errors and at the same time to find out how students receive and respond to teachers' oral corrective feedback, some observation sessions of the same learners also took place during oral expression, grammar and phonetics classes. The findings revealed that both learners and teachers have positive attitudes towards error correction and that teachers usually opt for the use of immediate recasts and explicit correction. Eventually, the hypothesis was confirmed, so in the light of this, teachers have to apply different oral corrective feedback strategies and learners should accept their errors to learn from them, and to avoid making errors, they need to practice the language more in order.